PARADIGMA AKTUALISASI DIRI ANAK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Suradi, Ahmad (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2017)
The essence of educational responsibility is the burden borne by someone, or a group regarding education as a result of something done, either because of concepts or ideas, words and actions or because they do nothing. Islamic education is actually very comprehensive in order to guarantee the results of quality Islamic education because deep education in the view of Islam is not only the realization of humanitarian responsibility but is a religious responsibility. Islamic education is a manifestation of family, community and government education synergistically. The realization of the responsibilities of each of the responsibilities of Islamic education institutions can be in the form of funding, personnel, teaching materials, ideas, information, the creation of conducive education, and educational infrastructure. Every person involved in education must account for the slightest burden both vertically (habl min Allah) and horizontally (habl min al-nas).